OPTIMIZATION OF INTERBUDGETARY RELATIONS WITHIN THE FRAMEWORK OF MUNICIPAL FORMATION - P.I. Ogorodnikov; V.V. Droshnev (Экономика региона, 2009)
The article is devoted a complex estimation of the basic directions of optimization revenue and expense parts of the budget by leader of municipal formation with provision for acting legislative bases, use of all spectrum of possible initiatives executive and legislature and modern scientific-practical innovative approaches of increase of investment attractiveness and competitiveness of administrative territory.